Social Impact Investing Opportunities in eHealth - Martin, Zsarnoczky; Fanni, Zsarnocky-Dulházi (Magyar Gerontológia, 2023)
In general, social impact investing may refer to providing capital to companies, organizations, and funds that are focused on solving critical societal or environmental problems. Social responsibility includes ideas that investors should balance profit-making with activities that benefit society as well because social impact investing focuses on positively impacting the society where it operates. Recently, large international companies reconsidering their motivation within their companies’ goal while their consumers purchase goods and services shifting their responsibility to profits and benefits. It seems small and medium-sized companies need also to develop ethics that guarantee the success of their activity with social responsibility issues. Therefore, for the most effectiveness of social impacts, the companies voluntarily have to operate under pressure from outside forces such as the conscious society.